اهمية معايير الجدارة الائتمانية للعميل المصرفي ومدى تطبيقها على التمويلات الاسلامية في المصارف الليبية. "دراسة ميدانية على عينة من المصارف الليبية المانحة للتمويل الاسلامي بمدينة سرت" (Economic studies journal, 2022)
This study aims to highlight the importance of international standards of creditworthiness for clients as well as the extent of their application to Islamic finances in Libyan banks. To achieve the objectives of the study, the descriptive analytical approach was relied on based on the field survey strategy. The study population included the Libyan banks that provide Islamic finances in Libya, however, given the similarity and convergence of the environment and nature of business and banking services provided by Libyan banks, the field study was limited to a sample of the branches of Libyan banks operating in the city of Sirte. Whereas, the information and primary data necessary to achieve the purpose of the study were collected from the credit officials of the studied banks sample, which numbered 30 people, through a questionnaire form which was analyzed by a number of appropriate statistical methods. This study concluded that the Libyan banks that provide Islamic finances apply only four criteria for creditworthiness in the credit assessment process for clients, arranged in order of importance, namely, Collateral, character of the client, Capacity and Purpose of credit, with a deficiency in the application of some factors related to the criterions of Character and capacity. While the banks completely neglected the criterions of capital, surrounding conditions and prospects. Accordingly, the study recommended the necessity of raising the degree of attention to all elements and criterions of creditworthiness in Libyan banks while granting Islamic finance in order to avoid the failure of its collection.
Keywords: creditworthiness; international standards of creditworthiness; Islamic finance